(untitled) (Research, Society and Development, 2023)
Tooth impaction is a common dental condition ranging from 0.8 to 3.6% of the general population. A tooth normally erupts when one-half to three-quarters of its final root length has developed. Impaction is usually diagnosed well after the tooth should have erupted. In this context, this article aims to review the literature about available treatments for impacted elements. For the construction of this article, a bibliographical survey was carried out in the databases SciVerse Scopus, Scientific Electronic Library Online (Scielo), U.S. National Library of Medicine (PUBMED) and ScienceDirect, with the help of the Mendeley reference manager. The articles were contemplated between the years 2000 to 2022. To perform a differential diagnosis for an impacted tooth, professionals must perform a clinical assessment of the patient’s condition. Informed consent should address treatment options for impacted teeth and complications associated with treatment. Four treatment options for managing impacted teeth have been described: observation, intervention, relocation, and extraction. There is some interaction between treatment options, and some options are only viable for a specific period of time. Before the dentist can recommend a suitable treatment plan for a patient, the dentist must perform a clear clinical and radiographic evaluation of the patient’s mouth, review the pathologic ramifications resulting from impacted teeth, discuss treatment complications with the patient, and address concerns. expressed by the patient.